Possible Involvement of the Nutrient and Energy Sensors mTORC1 and AMPK in Cell Fate Diversification in a Non-Metazoan Organism - Gross, Julian D.; Pears, Catherine J. (Frontiers in Cell and Developmental Biology, 2021)
mTORC1 and AMPK are mutually antagonistic sensors of nutrient and energy status that have been implicated in many human diseases including cancer, Alzheimer’s disease, obesity and type 2 diabetes. Starved cells of the social amoeba Dictyostelium discoideum aggregate and eventually form fruiting bodies consisting of stalk cells and spores. We focus on how this bifurcation of cell fate is achieved. During growth mTORC1 is highly active and AMPK relatively inactive. Upon starvation, AMPK is activated and mTORC1 inhibited; cell division is arrested and autophagy induced. After aggregation, a minority of the cells (prestalk cells) continue to express much the same set of developmental genes as during aggregation, but the majority (prespore cells) switch to the prespore program. We describe evidence suggesting that overexpressing AMPK increases the proportion of prestalk cells, as does inhibiting mTORC1. Furthermore, stimulating the acidification of intracellular acidic compartments likewise increases the proportion of prestalk cells, while inhibiting acidification favors the spore pathway. We conclude that the choice between the prestalk and the prespore pathways of cell differentiation may depend on the relative strength of the activities of AMPK and mTORC1, and that these may be controlled by the acidity of intracellular acidic compartments/lysosomes (pHv), cells with low pHv compartments having high AMPK activity/low mTORC1 activity, and those with high pHv compartments having high mTORC1/low AMPK activity. Increased insight into the regulation and downstream consequences of this switch should increase our understanding of its potential role in human diseases, and indicate possible therapeutic interventions.